Islamic Environmental Stewardship: A Sociological Approach to Hadith and Legal Frameworks for Ecological Responsibility - Salman, Abdul Matin bin; Asmanto, Eko (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2024)
This research analyzes the approach of Islamic law to environmental management through the study of Hadith from a sociological approach. The environment is an essential issue in the modern world, with various challenges related to nature conservation. Islamic law, mainly through the Hadith, provides moral and legal guidance on human responsibility towards the environment. This study explores how the Hadiths provide the basis for balanced and sustainable environmental management and how these principles can be analyzed using a legal sociology approach: the interaction between law and society. Using a qualitative method that combines the study of Hadith texts with sociological analysis, the study found a unity between Islamic law and social norms that promote environmental sustainability. Hadith underscores the importance of individual and collective responsibility in maintaining the balance of nature. At the same time, legal sociology highlights the role of community and social structure in implementing environmental rules. The results of this research aim to gain a deeper insight into the relevance of Islamic teachings in dealing with global environmental issues and to become the basis for developing a more holistic and integrated policy to preserve nature.